The Effect Of The Application Of Nomograph Pros On The Learning Outcomes Of Elementary School Students Materials Of Counting Intelligence Operations - Muh. Yazid; Muhammad Sururuddin; Baiq Yulia Kartika; Dina Apriana (Prodi PGMI IAIN Salatiga, 2021)
The purpose of this study was to determine the effect of the application of Nomograph teaching aids on student learning outcomes. This research was conducted at grade IV. The method used in this study is an experimental method with a one-group pre-test-post-test design. The instrument used in this study was a mathematics learning outcome test in the form of an essay. The test result data were analyzed by means of the t-test on the final result (post-test). Based on the analysis of the research data, there is an effect of the application of Nomograph teaching aids on learning outcomes.